2013
DOI: 10.1186/1471-2458-13-971
|View full text |Cite
|
Sign up to set email alerts
|

The association between family and community social capital and health risk behaviours in young people: an integrative review

Abstract: BackgroundHealth risk behaviours known to result in poorer outcomes in adulthood are generally established in late childhood and adolescence. These ‘risky’ behaviours include smoking, alcohol and illicit drug use and sexual risk taking. While the role of social capital in the establishment of health risk behaviours in young people has been explored, to date, no attempt has been made to consolidate the evidence in the form of a review. Thus, this integrative review was undertaken to identify and synthesise rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 69 publications
3
72
1
6
Order By: Relevance
“…dolescent development is typically facilitated in the socioecological context of stable family, school, and community networks, which can ameliorate psychological and behavioral problems and promote well-being (Biglan, Flay, Embry, & Sandler, 2012; Brooks, Magnusson, Spencer, & Morgan, 2012; McPherson et al, 2013). Child welfare services are intended to support such development by connecting youth to comprehensive resources through a combination of services and informal support, including maintenance of ties to family and community of origin.…”
Section: Introductionmentioning
confidence: 99%
“…dolescent development is typically facilitated in the socioecological context of stable family, school, and community networks, which can ameliorate psychological and behavioral problems and promote well-being (Biglan, Flay, Embry, & Sandler, 2012; Brooks, Magnusson, Spencer, & Morgan, 2012; McPherson et al, 2013). Child welfare services are intended to support such development by connecting youth to comprehensive resources through a combination of services and informal support, including maintenance of ties to family and community of origin.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 A recent meta-analysis exploring the role of social capital in the health of children and adolescents (including college-aged adults) reported that greater social capital was associated with better health outcomes related to physical activity, nutrition, and alcohol, tobacco and other drug use. 19 In the college-aged population, high social capital promotes protective health behaviors, including safer sex practices and less binge drinking and illicit drug use. 2022 Each of these health risk behaviors are linked to the development of various chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the potential determinants of health-risk behaviours such as smoking and drinking in young people is important for developing an effective prevention effort. In the field of public health, it is widely considered that social determinants play a significant role in health and health-related behaviours (McPherson et al 2013). Against this background, the present study focuses on social capital as an important social determinant of youth health-risk behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it has been proposed that high levels of social capital might influence health-related behaviours by promoting rapid diffusion of health information, increasing adoption of healthy behavioural norms, and exerting informal social control over deviant behaviours (Kawachi and Berkman 2000). Social participation in young people might exert an especially high influence over health-risk behaviours through expectations about the behavioural norms of the group they participate in (McPherson et al 2013); more specifically, participation in extracurricular activities is the most influential activity for enhancing students' school connectedness and might serve as a social control function deterring them from delinquency (Moilanen et al 2014). This study simultaneously examined the effects of social participation at both individual and school levels on youth health-risk behaviours, such as cigarette smoking and alcohol drinking, by measuring aggregate student responses to participation in each school's organized activities.…”
Section: Introductionmentioning
confidence: 99%